KERAGAMAN SPESIES LANDAK LAUT (Echinoidea) FILUM ECHINODERMATA BERDASAR MORFOLOGI DI PERAIRAN DOFA KABUPATEN KEPULAUAN SULA - Wirda A.Z. Umagap (UNIVERSITAS KHAIRUN, 2013)
Echinoidea is the invert animal which founded at intertidal and very important in the beach ecosystem. They have the gonad which high economis and useful by people around the island. This research aim to knowed about of Echinoidea diversity with morfologi at the Dofa marine district of Sula islands. The Echinoidea specimen from 3 point sampling which showed morfology and anatomy character, and then to identificated withÂ Monograph Of Shallow Water Indo-West Pacifik Echinoderms. The character of diagnosed which used to different species for shape, stark colour, skeleton form, and apical system.